Human Rights and the WTO: Issues for the Pacific - Joseph, Sarah (Victoria University of Wellington Law Review, 2009)
In the Pacific, Australia, New Zealand, Fiji, Papua New Guinea, Solomon Islands and Tonga are World Trade Organization members. This article examines the human rights concerns regarding the WTO, in particular the impact of WTO rules regarding trade liberalisation on poverty and development within developing states. The author comments on the costs of conditional WTO membership and the possible consequences of free trade and globalisation in the Pacific region.